2014
DOI: 10.1016/j.jtcvs.2014.02.084
|View full text |Cite
|
Sign up to set email alerts
|

Twist-related protein 1 negatively regulated osteoblastic transdifferentiation of human aortic valve interstitial cells by directly inhibiting runt-related transcription factor 2

Abstract: Our study results suggest that TWIST1 could play an important role in preventing human aortic valve calcification by negatively regulating osteoblastic transdifferentiation of human aortic VICs through direct inhibition of RUNX2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…32 Conversely, twist-related protein 1 negatively regulates osteoblastic transdifferentiation of human VICs by directly inhibiting Runx2. 33 Accumulating evidence has shown that miRNAs repress gene expression through their ability to pair with target regions in the 3 0 -UTRs of the mRNAs. 34 In this study, several lines of evidence exist to support Runx2 as a direct target of miR-204 in VICs: First, miR-204 binds to Runx2 through complementary binding of the miR-204 seed sequence, which is complementary to 3 0 -UTR of Runx2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…32 Conversely, twist-related protein 1 negatively regulates osteoblastic transdifferentiation of human VICs by directly inhibiting Runx2. 33 Accumulating evidence has shown that miRNAs repress gene expression through their ability to pair with target regions in the 3 0 -UTRs of the mRNAs. 34 In this study, several lines of evidence exist to support Runx2 as a direct target of miR-204 in VICs: First, miR-204 binds to Runx2 through complementary binding of the miR-204 seed sequence, which is complementary to 3 0 -UTR of Runx2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from P2Y2 À/À mice are prone to osteoblast differentiation. 100 Zhang, 2014 Human, from noncalcified areas of calcified valves Transcription factor Twist Osteogenic medium upregulates Twist. Overexpression of Twist decreased other calcification genes, and Twist siRNA triggers osteoblast differentiation.…”
Section: Tnf-related Apoptosis-inducing Ligand (Trail)mentioning
confidence: 99%
“…Overexpression of TWIST in VICs decreased expression of Runx2, osteocalcin, osteopontin, and ALP, whereas the knockdown of Twist with siRNA had the opposite effect. 100 Hyaluronan is one of the abundant components of the extracellular matrix in connective tissues, including the aortic valve leaflets. Porcine VICs grown on collagen were found to secrete hyaluronan, and adding exogenous hyaluronan at the mean molecular weight of 64 kDa to the medium reduced nodule formation, although the higher and lower molecular hyaluronan did not have this effect.…”
Section: Miscellaneous Factorsmentioning
confidence: 99%
“…There are few studies demonstrating methods capable of highly efficient gene delivery to VICs, though many strategies have been reported. Lipid-based reagents that have been used for nucleic acid delivery to VICs include Lipofectamine 2000, a cationic lipid formulation to deliver DNA, 4 siRNA, [5][6][7][8] and miRNA mimics 6 ; Dharmafect1, a cationic lipid-based vehicle for siRNA delivery 9 ; and HiPerfect, a cationic lipid reagent, for siRNA delivery. 10,11 Transfection reagents comprising lipids combined with other reagents have also been used, such as Oligofectamine, a lipid-polymer blend for siRNA delivery 12 and Turbofectin 8, a lipid-histone blend for DNA delivery.…”
Section: Introductionmentioning
confidence: 99%
“…siRNA delivery by Lipofectamine and N-TER were reported to reach *90-100% of VICs, measured by the presence of nontargeting fluorophore-labeled siRNA. 5,13 However, the efficiency of siRNA uptake may be misleading because it does not correlate with functional siRNAmediated RNA interference. 41 Gene delivery by ssAAV involves a rate-limiting step of second-strand synthesis before transgene expression can occur.…”
mentioning
confidence: 99%